A rare encounter with acute epiglottitis - Lok, Florence Yan Lee; Chan, Patrick Wai Kiong; Goh, Adrian Yu Teik (Faculty of Medicine, University of Malaya, 2001)
We describe a rare encounter with a 6-year old Indian boy admitted with acute epiglottitis due to Haemophilis influenzae. Acute epiglottitis is an uncommon cause of life threatening upper airway obstruction and a rare presentation of invasive Haemophilus influenzae type b (Hib) disease in this region, compared to the more developed West. The cause for this observation is often attributed to differences in the genetic predisposition and socio-economic parameters. The organism subtype and the host response have been shown to determine the type of invasive Hib disease. However, the evidence to explain this difference is poorly understood and remains and intriguing enigma